2021
DOI: 10.3389/fpls.2021.691211
|View full text |Cite
|
Sign up to set email alerts
|

Introgression of Maize Diversity for Drought Tolerance: Subtropical Maize Landraces as Source of New Positive Variants

Abstract: Current climate change models predict an increased frequency and intensity of drought for much of the developing world within the next 30 years. These events will negatively affect maize yields, potentially leading to economic and social instability in many smallholder farming communities. Knowledge about the genetic resources available for traits related to drought tolerance has great importance in developing breeding program strategies. The aim of this research was to study a maize landrace introgression pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Due to the inclusion of DH lines derive from crosses of selected inbred lines in the panel, we observed moderate structure in the present study. Several researchers also been reported moderate structure in the tropical maize germplasm [ 29 , 31 , 37 , 53 , 54 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the inclusion of DH lines derive from crosses of selected inbred lines in the panel, we observed moderate structure in the present study. Several researchers also been reported moderate structure in the tropical maize germplasm [ 29 , 31 , 37 , 53 , 54 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Semagn et al [ 2 ] reported four meta-QTLs associated with grain yield for both under drought and optimum management. The high QTL detection power and fine resolution of mapping are exploited by joint linkage association mapping in multiple biparental populations [ 28 , 29 , 30 ]. The identification and validation of novel genomic regions associated with economically important traits under WW and WS as well as MLN are important to accelerate the development of climate-resilient improved maize varieties to enhance high maize productions in smallholder families and contribute to food security [ 12 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that the landraces are adapted to a specific environment and region [91]. Furthermore, the main reason to use landraces is to bring novel favorable alleles to a breeding population [92]. The local landraces are rich in diverse genetic materials and are a good source of important genes such as resistance to biotic and abiotic stresses and quality traits [91] and have a better capacity to absorb and utilize N under low N fertilization conditions [93].…”
Section: Discussionmentioning
confidence: 99%
“…However, the improvement of NUE in maize cultivars is a great challenge due to the genetic complexity and strong interaction with the environment. Thus, information on the genetic control governing the inheritance of traits would be useful for crop researchers to choose the breeding method for obtaining NUE efficient cultivars [20] and to develop breeding program strategies for traits related to drought tolerance [92]. Therefore, assessment of combining ability and heterosis is of utmost importance for breeding hybrid maize [112], so that the genotypes could be successfully used to develop hybrids with superior NUE under diverse environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress is reported to prolong the anthesis–silking interval, reduce kernel set [ 9 , 10 , 19 , 20 ], decrease photosynthetic rate and chlorophyll content [ 14 , 19 , 21 ], and lead to damaged cellular membrane [ 22 ]. Conversely, drought and or terminal drought at seedling stage has deleterious impacts on seedling establishment, vegetative growth, photosynthesis, root growth, anthesis, anthesis–silking interval, pollination, and grain formation in maize [ 23 , 24 ]. Combined heat and drought is well documented to reduce photosynthetic efficiency, stomatal conductance, leaf area, water use efficiency, and ultimately grain reduction [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%